Internal Migration and Household Consumption in Ghana - Ranzani, Marco; Pavelesku, Dan (World Bank, Washington, DC, 2015)
Over the past two decades Ghana has seen a rapid increase in internal migration. Census data show that internal migration increased from 38.6 percent to 43.3 percent between 2000 and 2010. According to the latest Ghana Living Standard Survey (GLSS) 2012/13, half of the migrants surveyed had migrated after 2003.